Association Between Food Plastic Packaging and Dysmenorrhea in Female Adolescents - Maghrifi, Dhini Safira; Lestari, Pudji; Sa’adi, Ashon (Journal of Maternal and Child Health, 2022)
Background: Most women experience certain pain and difficulty during menstruation or what is known as dysmenorrhea. Dysmenorrhea is a gynecological problem and is the most frequently reported chief complaint in women. Dysmenorrhea is defined as cramping in the lower abdomen that occurs before or during menstruation. The use of plastic as food and beverage packaging is still a commonly used in the community. Plastic contains several compounds, including phthalates and bisphenol-A (BPA) which have potential as endocrine disrupting chemicals (EDCs). Menstruation and dysmenorrhea are closely related to hormonal system disorders. This study aims to analyze the relationship between food plastic exposure and the incidence of dysmenorrhea among adolescents.Subjects and Method: The design in this study is observational analytic with a cohort approach. This study was conducted at the Faculty of Medicine, Universitas Airlangga with a population of midwifery students. The sampling technique used was total sampling with a total of 149 subjects. The dependent variable was. dysmenorrhea. The independent variable was food plastic exposure. The instruments used were a visual analogue scale (VAS) questionnaire and a food plastic exposure questionnaire. The data collection was taken in 2 menstrual cycles. Data were analyzed by chi-square test.Results: The results showed that 71.8% of the subjects experienced moderate level of exposure to food plastic. Dysmenorrhea reported that 128 subjects (86%) had dysmenorrhea. In VAS assess-ment, most of the subjects which was 43% experienced mild pain. This study showed that there was a relationship between exposure to plastic food and the incidence of dysmenorrhea in adolescents (p= 0.049).Conclusion: There is a relationship between exposure to plastic food and the incidence of dysmenorrhea in adolescents.